Crossing and Transgressing Borders in The Heart of Midlothian - Sabiron, Céline (Romanticism and Victorianism on the Net, 2009)
If the 1707 Act of Union removed the immaterial legal and political border between England and Scotland by merging them into the single kingdom of Great Britain, it could not erase the almost impassable natural boundary dividing the twin sisters. This tangible geographical barrier remained as a magnificent reminder of a former separation, thus questioning the disappearance of the national frontier.The confrontation between abstract and concrete boundaries, which is at stake in historical Scotland, is staged in Walter Scott’s The Heart of Midlothian set a few decades after the Union. The heroine’s physical journey across the Anglo-Scottish border gradually takes on a more symbolic significance as she trudges through the marches to redeem her sinful sister.In studying the novel, I will analyse the series of embedded tangible boundaries present on the British territories and show how they are constantly crossed by the protagonists. This physical crossing of concrete borders often goes with the mental crossing of abstract barriers. Overstepping a physical boundary can lead to transgressing moral and societal limits as it is exemplified with the Scottish Borders, a den of iniquity and unlawful transactions. External borders can thus embody more internal boundaries and serve to map territories of the mind.